The last victim ebook A novel. - Robards, Karen (Dr. Charlotte Stone,, 2012)
“[An] exceptional storyteller . . . Leave it to [Karen] Robards to deliver the start of a series that is distinctive and unforgettable!”— RT Book Reviews   A sought-after expert in criminal pathology, Dr. Charlotte Stone regularly sits face-to-face with madmen. At the age of sixteen, she herself survived a serial killer’s bloodbath. Because of the information she gave police, the Boardwalk Killer went underground, but Charlie kept her postmortem visions of the victims to herself. Years later, to protect her credibility as a psychological expert, she tells no one about these apparitions. Now a teenage girl is missing, her family slaughtered. The Boardwalk Killer—or a sick copycat with his M.O.—is back. This is the one case Charlie knows she shouldn’t go near. But she also knows that she may be the one person in the world who can stop this vicious killer, especially when she receives help from an unexpected source: The fiery spirit of a seductive bad boy who refuses to be ignored.   “Excellent . . . This story is going to haunt you.”— Pittsburgh Post-Gazette   “Thrilling . . . a fun and sexy read.”— Booklist   “Tantalizing.”— Library Journal   Features a preview of the next Charlotte Stone novel, The Last Kiss Goodbye .